2022
DOI: 10.3389/fimmu.2022.871463
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the common cold to be a live-attenuated SARS-CoV-2 vaccine

Abstract: According to the American Centers for Disease Control and Prevention, people in all age groups catch two or more “colds” per year, at least half of which are caused by human rhinoviruses. Despite decades of effort, there are no vaccines or drugs against rhinovirus infections and even social distancing measures that were effective in reducing the spread of the pandemic coronavirus, SARS-CoV-2, did not reduce the rate of rhinovirus detection. Fortunately, most rhinovirus strains are naturally attenuated in that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Physical distancing seems to be not effective in reducing the transmission of this virus. But, it is essential to notice that rhinovirus infection is not associated with a significant rate of hospitalization or death [ 160 ]. Several researchers have demonstrated that daily dosing of 1 million IU of intranasal IFN-alpha gave 75–87% protection against rhinovirus infection [ 161 , 162 ].…”
Section: Clinical Trials For Respiratory Virus Infectionmentioning
confidence: 99%
“…Physical distancing seems to be not effective in reducing the transmission of this virus. But, it is essential to notice that rhinovirus infection is not associated with a significant rate of hospitalization or death [ 160 ]. Several researchers have demonstrated that daily dosing of 1 million IU of intranasal IFN-alpha gave 75–87% protection against rhinovirus infection [ 161 , 162 ].…”
Section: Clinical Trials For Respiratory Virus Infectionmentioning
confidence: 99%
“…It can be difficult to distinguish COVID -19 from other respiratory viral infections by looking only at the following the patient's symptoms. 34,51 COVID-19 shares symptoms with several other respiratory viruses, such as fever, cough, and sore throat. 32 This makes diagnosis more difficult and requires thorough testing for multiple viruses.…”
Section: Viral Co-infectionmentioning
confidence: 99%
“…Rhinoviruses are highly infectious in humans and cause the common cold with mild symptoms in most of the infected individuals. Their low pathogenicity and high contagion rate could make them suitable vectors for viral vaccines, such as for SARS-CoV-2 [ 206 ]. Another possibility is to develop LAVs vaccines based on a seasonal cold coronavirus with high homology to SARS-CoV-2.…”
Section: Indirect Dispersion Of Live-attenuated Virus Vaccinesmentioning
confidence: 99%